Attenuation And Scattering Studies Of Natural And Fabricated Particleboard Of Rhizophora Spp.in The 15.77 - 25.27 Key Photon Energy Range - Shakhreet, Bassam Zuhdi Othman (2006)
Mass attenuation coefficients of Rhizophora spp. were determined in the photon energy range of 15.77 - 25.27 keV using a method based on X-ray fluorescence (XRF) with a system setup in L-shape geometry and utilizing a SiPIN detector. The performance of each individual component in the setup was tested separately and its characteristics recorded for optimal use. The XRF system was then examined as an integrated assembly. To provide electron density information in support of the introduction of new tissue equivalent materials for mammography phantoms, the electron density of Rhizophora spp. wood was also measured and determined. The measured value (3.183 ± 0.003) x 1023 e/cm3 at photon energies 15.77, 17.48 and 22.16 keV is reasonably close to the calculated value of (3.195 x 1023 e/cm3 ). Furthermore, the accuracy of the values is good. In general, the electron density of water (3.341 x 1023 e/cm3 ) and the electron density of values for breast tissues ranging from (3.120 - 3.510) x 1023 e/cm3 (ICRU, 1992) are comparable to the measured Rhizophora spp. values. The linear and the mass attenuation coefficients of natural Rhizophora spp. phantom from three different parts of one tree (top, middle, and bottom) were determined in the photon energy range of 15.77 to 25.27 keV.